Platelet-Rich Plasma: Principles and Applications in Plastic Surgery - Abu-Ghname, Amjed; Perdanasari, Aurelia Trisliana; Davis, Matthew J.; Reece, Edward M. (Seminars in Plastic Surgery, 2019)
Platelet-rich plasma (PRP) is an autogenously harvested liquid platelet concentrate extracted from a patient's peripheral blood that contains higher than baseline concentrations of growth factors and cytokines. This innovative new technology has demonstrated great promise in the field of plastic surgery, and its use has been evaluated in several clinical settings including wound healing, hair restoration, and skin rejuvenation. The goal of this article is to explain the biology behind PRP and to review the basic principles involved in its preparation. This will be followed by a discussion of some clinical applications of PRP in both aesthetic and reconstructive plastic surgery.
Keywords: platelet-rich plasma; PRP; growth factors; wound healing; skin rejuvenation; bone healing; hair growth